Gold Particles Recovery using Novel Reducing Agent with Regard to Continuous Approach - Fotovat, Alireza; Feizbakhsh, Alireza; Garmaroudi, Ali B. (Current Nanoscience, 2022)
Background: Over 300 tonnes of gold are utilised in electronic devices every year all over the world. End-of-life of these electronic equipments offers a crucial recycling potential as a secondary gold supply. Electronic boards are among common and exploitable gold sources that are widely used in various industries. The aim of this paper is to use the gold element of electronic boards by adjusting its surface functionality and also its particle size to make this metal an adequate material to be used in various applications. Methods: To achieve this purpose, by using acidic solutions and via up to bottom chemical synthesis method among physical, chemical, and biological methods and in addition, by transferring gold particle size from micrometer to nanometer (to gain good nano-dimension properties), the surfacearea- to-volume ratio will experience an increase such that new structural properties emerge, change, or improve. Results: Analysis of the results using Fourier-Transform Infrared spectroscopy, X-Ray Diffraction, and Field Emission Scanning Electron Microscopy have confirmed high-quality production and proper extraction of gold particles on a nanometer scale from electronic plates and confirmed the crystalline structure of extracted gold in the particle size range of 70-110 nm. Conclusion: The main objective of this research is to derive and fabricate gold nanoparticles using oxidative chemical route using HCl and Aqua regia to produce gold nanoparticles on Nano dimension scale. Results have shown that gold nanoparticles are synthesized successfully via a chemical process. Moreover, acid concentration and reaction time have an enormous effect on the gold nanoparticle production procedure.
Keywords: experimental design